Real-Time Imaging and Quantification of Peptide Uptake in Vitro and in Vivo - Karatas, Hacer; Maric, Tamara; D’Alessandro, Pier Luca; Yevtodiyenko, Aleksey; Vorherr, Thomas; Hollingworth, Gregory J; Goun, Elena A (ACS chemical biology, 2019)
Peptides constitute an important class of drugs for the treatment of multiple metabolic, oncological, and neurodegenerative diseases, and several hundred novel therapeutic peptides are currently in the preclinical and clinical stages of development. However, many leads fail to advance clinically because of poor cellular membrane and tissue permeability. Therefore, assessment of the ability of a peptide to cross cellular membranes is critical when developing novel peptide-based therapeutics. Current methods to assess peptide cellular permeability are limited by multiple factors, such as the need to introduce rather large modifications (e.g., fluorescent dyes) that require complex chemical reactions as well as an inability to provide kinetic information on the internalization of a compound or distinguish between internalized and membrane-bound compounds. In addition, many of these methods are based on end point assays and require multiple sample manipulation steps. Herein, we report a novel “Split Luciferin Peptide” (SLP) assay that enables the real-time noninvasive imaging and quantification of peptide uptake both in vitro and in vivo using a very sensitive bioluminescence readout. This method is based on a straightforward, stable chemical modification of the peptide of interest with a d-cysteine tag that preserves the overall peptidic character of the original molecule. This method can be easily adapted for screening peptide libraries and can thus become an important tool for preclinical peptide drug development.